Gambaran Prokrastinasi Tugas Akhir Pada Mahasiswa Semester Akhir di Universitas Sahid Surakarta - Dava Bagas Indianto; Sri Ernawati; Dhian Rizkiana Putri (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Final assignment procrastination is the tendency to postpone academic activities related to the final assignment. This research aims to see the picture of final assignment procrastination at Sahid University, Surakarta. The research method used is a qualitative method by means of observation and interviews. The informants in this research consisted of 7 (seven) students with active status, semester 8 and above, who were taking their final assignment. The informants consisted of 3 men and 4 women. Based on the results of research that has been carried out, it was found that 85% of students at Sahid University Surakarta who took final assignments experienced final assignment procrastination. This is influenced by students' lack of ability to manage their time between studying and working part-time. Other factors that cause student procrastination include lack of motivation and not having a priority scale.